MODEL MATEMATIKA REAKSI SINTESIS DIASILGLISEROL MENGGUNAKAN BIOKATALIS MELALUI MEKANISME ESTERIFIKASI TAK REVERSIBLE - Hermansyah, Heri; Utami, Tania Surya; Prianto, Fajar Achmadi (UI Scholars Hub, 2011)
Mathematical Model for Synthesis Reaction of Diacylglycerol by Irreversible Esterification Mechanism. Diacylglycerol, a component of natural oil has beneficial physiological function, mainly as oil with anti-obesity and anti fat accumulation effect. Several studies for efficient synthesis of diacylglycerol have been done by researchers in Japan. Esterification of fatty acid and glycerol using biocatalyst has been used as an effective synthesis process on it was industrial scale. A kinetics model for diacylglycerol synthesis was proposed, however, it was very specific so that not appropriate to be applied in different condition. In this study, a model for diacylglycerol synthesis by stepwise esterification of glycerol by fatty acid based on general assumption and condition is proposed. Runge-Kutta method is used in numerical calculation of substrate concentration. This model is useful for predicting behaviors of substrate at esterification of fatty acid and glycerol which is difficult to be measure experimentally, also as prediction in system design for diacylglycerol synthesis at different scale.